2021
DOI: 10.1177/14680874211022292
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the effects of intake charge on oxy-fuel combustion in a dual-injection spark ignition engine at economical oxygen-fuel ratios

Abstract: In order to decrease Carbon Dioxide (CO2) emissions, Oxy-Fuel Combustion (OFC) technology with Carbon Capture and Storage (CCS) is being developed in Internal Combustion Engine (ICE). In this article, a numerical study about the effects of intake charge on OFC was conducted in a dual-injection. Spark Ignition (SI) engine, with Gasoline Direct Injection (GDI), Port Fuel Injection (PFI) and P-G (50% PFI and 50% GDI) three injection strategies. The results show that under OFC with fixed Oxygen Mass Fraction (OMF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Over the last decade, Wu et al provided valuable inputs into OFC research, which indicated that the power, fuel economy, and emissions could be improved through optimization strategies in the ICRC port fuel injection (PFI) engine fueled with propane. Li et al , explored the potential of the intake charge to optimize combustion and performance of the OFC SI engine fueled with gasoline.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, Wu et al provided valuable inputs into OFC research, which indicated that the power, fuel economy, and emissions could be improved through optimization strategies in the ICRC port fuel injection (PFI) engine fueled with propane. Li et al , explored the potential of the intake charge to optimize combustion and performance of the OFC SI engine fueled with gasoline.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal efficiency and indicated work could be enhanced by an appropriate rate of EGR matches with ignition timing and increased WI temperature. Li et al [26] initially investigated the impacts of intake charge on OFC in a dual-injection SI engine fuelled with gasoline under GDI, P-G and PFI three injection strategies.…”
Section: Introductionmentioning
confidence: 99%